A Band That Causes Leaky Valves: Severe Mitral Regurgitation due to Left Atrial Fibrous Band—A Case Report and Literature Review - Christopher Nnaoma; Gurdarshan Sandhu; Christoph Sossou; Ilan Vavilin; Jose Bustillo; Anshu Garg (Case Reports in Cardiology)
Left atrial fibrous band is a rare clinical and echocardiographic finding characterized by the presence of a fibrous band attached to the mitral valve. Diagnosis is accomplished with transesophageal echocardiography (TEE), live 3D imaging, or cardiac MRI. Most patients are asymptomatic and incidental findings. However, in rare cases, an atrial fibrous band can produce symptoms such as dyspnea on exertion, fatigue, and lightheadedness secondary to mitral regurgitation (MR) which can lead to heart failure if unattended to. More serious complications such as cardioembolic phenomenon can occur. We herein report a case of a 55-year-old male with hypertension who presented with dyspnea on exertion and chest pain. Transthoracic echocardiography (TTE) showed mitral valve prolapse with moderate to severe mitral regurgitation. TEE showed an atrial fibrous band. Given the patient’s poor exercise tolerance, he was taken to surgery for a mitral annuloplasty.